The pattern-matching approach and its application in tourism development - Vaughan, David Roger; Andriotis, Konstantinos (My University, 2009)
Tourism development cannot be fully understood and validated from a positivist perspective without the testing of theory against empirical evidence. Thus the pattern-matching approach studies phenomena on the basis of facts and observations relevant to the testing of theories and models. This paper tests two selected tourism development theories, diffusion and dependency, against empirical evidence from Crete. In doing this, it has three main objectives: to set out the nature of the pattern-matching approach; to illustrate the application of the pattern-matching approach, in an exploratory way, and to evaluate the approach based on the evidence of the exploratory application.
Keywords: Pattern-matching approach; Development theory; Case study; Tourism; Crete